Sosialisasi Pentingnya Penerapan OBE (Outcome-Based Education) Pada Perangkat Pembelajaran Sekolah di Kecamatan Batukliang - Muhsinun, Muhsinun; Rasyidi, Mulia; Azizi, Asrorul; Muttaqin, Muh. Zaini Hasanul; Sumardiana, Sumardiana; Arianti, Dina; Fitriani, Esi (Lembaga Publikasi Ilmiah Nusantara, 2025)
The purpose of this community service initiative was to socialize the importance of implementing Outcome-Based Education (OBE) in teaching materials at schools in the Batukliang District. The activities began with a needs assessment through surveys and interviews with teachers in the region, which revealed that their understanding of OBE was still limited. Subsequently, intensive training was conducted to provide a solid understanding of the fundamental concepts of OBE and how to implement them in the development of syllabi, Lesson Plans (RPP), and competency-based assessments. After the training, teachers applied the knowledge they had gained in their classroom teaching and provided feedback on the challenges they faced, particularly in developing competency-based evaluations. The training results indicated an improvement in the teachers' understanding of the OBE concepts and their application, although some challenges remained, such as time constraints, limited resources, and difficulties in creating holistic assessments. The support of school principals also proved crucial in ensuring the successful implementation of OBE. The post-training evaluations showed that the teachers found the activities valuable and felt that their skills in designing OBE-based learning had improved. Overall, this community service initiative successfully enhanced the quality of teachers' understanding and skills in implementing OBE in the Batukliang District. It is hoped that this initiative can serve as a model for other regions, with the goal of improving the quality of education that is relevant to the demands of the workforce.